Preservation technique to identify Bactrocera dorsalis complex (Diptera: Tephritidae) based on image analysis - Rika Alfianny; Ardhiani Kurnia Hidayanti; Tati Suryati Syamsudin (Jurnal Entomologi Indonesia, 2022)
Fruit flies (Bactrocera dorsalis (Hendel)) are insect pests of many fruits and vegetables. Yield losses due to this pest can reach 100%, and many may be unaware that fruit flies are the trigger for several disease attacks on crops such as fungi and bacteria. This study aimed to identify the most appropriate preservation technique for morphological identification of B. dorsalis by image analysis. Images were taken with the Nikon DSF12 Trinocular Microscope. The methods used varied by trapping period (short-term and long-term) and types of preservatives (ethanol and propylene glycol). Specimens were obtained from Bandung and Sumedang Regency. Results demonstrated that ethanol-based preservation was the most appropriate to acquire the abdominal image of B. dorsalis obtained via short-term trapping, meanwhile a propylene glycol-based preservation was suggested for specimens trapped using longer-term methods.